ANALISIS KEDALAMAN AKUIFER AIR TANAH DENGAN METODE GEOLISTRIK DI DISTRIK SENTANI KOTA KABUPATEN JAYAPURA - BLESKADIT CHATERINE DAMAYANTI; VIRMAN VIRMAN; JOHNSON SIALLAGAN (Jurnal Ilmu Pendidikan Indonesia, 2020)
Geophysical research on geoelectric method configuration schlumburger has been carried out in Sentani Kota area, Jayapura district to analyze the depth of groundwater aquifers. The data consisted of seven points measurement spread in Sentani Kota areas namely Kampung Harapan, Hawaii, Kampung Sereh, Kompleks 751, Pasar Lama, Doyo Baru, and Kampung Toware. The data obtained was done by processing data with IP2WIN software, and then made a subsurface profile likes log. Based on data processing, the results obtained showed that in Kampung Harapan the potential groundwater aquifer was found with a resistivity value of 18 Ωm at a depth of > 17.9 m. In the Hawaiian area potential groundwater aquifers are found with resistivity values of 8.92 Ωm at a depth of 64.7 m. In the Kampung Sereh area potential groundwater aquifers were found with resistivity values of 14 Ωm at a depth of 24 m. In the complex area of 751 a depressed groundwater aquifer is found in two layers with a third layer resistivity value of 106 Ωm at a depth of 13.3 m and a fifth layer 81.8 Ωm at a depth of >28.6 m. In the Pasar Lama area groundwater aquifers were found with resistivity values of 102 Ωm at depths > 17.4 m. In the Doyo Baru area, a potential depressed groundwater aquifer was found with a resistivity value of 50.1 Ωm at a depth of 123 m. And in the Kampung Toware a potential groundwater aquifer is found with a resistivity value of 11.5 Ωm at a depth of >27.7 m. From the results of the study, in the Sentani City area, groundwater aquifers were arranged by lithology of sandstone.